Distribution of α-Cellulose, Hemicelluloses and Acid Insoluble Lignin During Total Chlorine Free Bleaching of AS/AQ Wheat Straw Pulp - Yaqoob, Naila; Stack, Karen; J. Cheema, Kausar; Rashed Hameed, Sahabzada; Mateen, Bushra (Asian Journal of Chemistry, 2011)
The effect of each individual bleaching stage on the percentage composition of α-cellulose, acid insoluble lignin and hemicelluloses in multistage total chlorine free bleaching of alkaline sulphate/anthraquinone (AS/AQ) wheat straw pulp was studied by using standard TAPPI and GC methods, respectively. With AOOxP bleaching, > 85 % of pulp fibers were calculated to be composed of true cellulosic fibers, while acid insoluble lignin (%) contents decreased to as low as < 2.0 % as compared to an unbleached sample where pulp fiber constitutes 76.6 % α-cellulose and 7.6 % acid insoluble lignin. A statistical correlation was established and it was found that hemicelluloses are also responsible for ageing of pulp. Burst and tensile index were also found to be effected by changes in hemicelluloses (%) in pulp structure.